Circulating MicroRNA Expression Profiles to Identify a Potential Link Between Prostate Cancer and Obesity - Arışan, Serdar; KILBAŞ, PELİN ÖZFİLİZ; RENCÜZOĞULLARI, ÖZGE; Ünsal, Narcin Palavan; Çoker-Gürkan, Ajda; Uysal-Onganer, Pınar; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Elsevier, 2022)
Effective diagnostic methods are needed to apply appropriate treatment strategies in patients with aggressive prostate cancer. From this point of view, risk factors that cause prostate cancer or its aggressiveness should be considered. Obesity is a critical risk factor for triggering prostate cancer's metastatic properties. microRNAs are used as biomarkers in diagnosing cancer and obesity depending on their tissue-specific expression patterns. This study investigates the role of obesity in the metastatic profile of prostate cancer depending on the differential expression signatures of selected miRNAs in prostate cancer and obese patients. The roles of miR-100, miR-141 and miR-145 in prostate cancer and obesity are partially known. However, their potential to become circular biomarkers in the blood is not elucidated. There is no previous data on miR-4463 and miR-653 on prostate cancer and obesity association. In this study, the blood samples were taken and obtained serum from 69 patients of 6 subgroups that consisted of one healthy group and five unhealthy groups based on their different prostate cancer or obesity levels. Five selected miRNA expression analyses (miR-100, miR-141, miR-145, miR-4463, and miR-653) were performed through total RNA isolation, which was confirmed via synthetic cel-miR-39 miRNA. Quantitative Real-Time PCR analyzed the expression levels of selected miRNAs. Data analysis was performed via normalising target miRNA expression levels with cel-miR-39. In this study, we found that the relationship between prostate cancer and obesity was investigated at the molecular level. It was suggested that target miR-100 could be a promising biomarker for non-obese and aggressive prostate cancer patients. miR-145 is a more potential biomarker than miR-141 for non-aggressive and non-obese patients. miR-4463 can be used to predict more prostate cancer patients than obese patients. Lastly, miR-653 can be a biomarker for non-aggressive prostate cancer cells.
Keywords: Prostate Cancer; Obesity; miR-100; miR-141; miR-145; miR-4463; miR-653